(3TQM GdaQGFV GdSLGhfOjIs - (3GdJhbGOj GdESJGfHhdj GdYKeGfj GdMfaj, GHf ceGd HGTG, ceGd HGTG RGOg, TeS GdOjf, CMeO Hf SdjeGf Hf ceGd HGTG, (B940 (3g`s ((3eOQSI bHdhMGLjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg Gdedc GdYdGe hHYO aEfj deG aQZJ ef JUMjM GdeNJUQ GdeDda aj Yde GdaQGFV GdefShH Edi GdSLGhfOjs
(3BNQgG (B:s
(3ef Pdc GdHGbj GdSOS hddHfJ GdfUa hGdHGbj ddehdi dCf cdG efgeG dG jQK ef UGMHg eG hQK cd efgeG YTQhf hdHfJ cd efgeG SJhf hddehdi YTQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 133s
(3eYLe GdeDdajf (B1 / 148s
(3cTa GdXfhf (B2 / 12487s
(3TPQGJ GdPgH (B8 / 238s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdaQGFVs